Sociopragmatic and Sociolinguistic Aspects of the Study of Discourse - Azamatovna, Yarmatova Mehriniso (International Journal on Integrated Education, 2023)
This article discusses how the language is studied in close connection with a person, his consciousness, thinking, spiritual and practical activities. Based on this material, it can be argued that sociopragmatics is the study of the socio-cultural aspects of the implementation of the communicative ability of an individual.